Effects of Mindfulness-Based Stress Reduction Programs on Chronic Pain Management in Elderly Patients in Tanzania - Chande, Sumari (American Journal of Health, Medicine and Nursing Practice, 2024)
Purpose: The aim of the study was to assess the effects of mindfulness-based stress reduction programs on chronic pain management in elderly patients in Tanzania. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study observed that participation in MBSR programs led to notable improvements in pain reduction and overall well-being. The program, which incorporates mindfulness meditation, body awareness, and yoga practices, facilitated a significant decrease in reported pain levels among participants. Moreover, individuals undergoing MBSR reported enhanced coping mechanisms for managing pain-related distress, improved functional abilities, and greater satisfaction with their daily activities. These findings suggest that MBSR interventions hold considerable promise as an effective non-pharmacological approach to chronic pain management in the elderly population, offering holistic benefits beyond mere symptom alleviation. Implications to Theory, Practice and Policy: Biopsychosocial model of pain, self-efficacy theory and neuroplasticity theory may be used to anchor future studies on assessing the effects of mindfulness-based stress reduction programs on chronic pain management in elderly patients in Tanzania. Implement culturally adapted MBSR programs that take into account the unique needs, preferences, and cultural backgrounds of elderly patients. Advocate for the integration of MBSR programs into healthcare policies and guidelines for chronic pain management in elderly populations.